Company accounting and financial statements - De Lange, Paul.; Yates, Lindsay; Rodgers, Robert (Melbourne : Thomas Nelson, 1994)
This book is about: Accounting for share and debenture issues; Accounting for the conversion of a business to a company; Accounting for company income tax; Finalisation of company accounts; Corporate reporting; ...
Keywords: Accounting; Economics; Corporations; Corporations -- Accounting; Corporations -- Accounting -- Problems, exercises, etc; Financial statements -- Problems, exercises, etc; Financial statements